Parameter Configuration in Bluetooth Mesh: Performance and Limitations - Mäkinen, Teemu (My University, 2025)
Development of Internet of Things (IoT) networks requires careful planning, not only to meet application specifications but also to maximize performance. Selecting a suitable communication technology can be a challenging task, but it is only one part of the process. Optimization of technology-specific parameters plays a significant role in achieving desirable results for different application use cases. This thesis studies a networking technology known as Bluetooth Mesh, focusing on its configurability. The effects of various important parameters are assessed through an experimental evaluation, which involves different network scenarios aiming to consider variations in network density, coverage area, and traffic intensity. Communication reliability and latency are the primary performance statistics to be considered, although other important aspects, such as energy consumption, are examined as well. Additional attention is given to underlying limitations that largely define the overall dimensions of system configuration, especially in terms of memory usage.
Keywords: bluetooth, mesh, configuration, wireless, iot, performance